Outcome of Simultaneous Arthroscopic Anterior Cruciate Ligament and Posterior Cruciate Ligament Reconstruction With Hamstring Tendon Autograft: A Multicenter Prospective Study - Panigrahi, Ranajit (Asian J Sports Med, 2016)
BACKGROUND: Multiligamentous injuries of knee are a complex problem in orthopaedics. Combined ACL-PCL injuries are uncommon, usually associated with knee dislocations. Extremity vascular status is essential because of possible arterio-venous compromise. These complex injuries require a systematic evaluation and treatment. Single setting simultaneous arthroscopic ACL and PCL reconstruction or a staged approach can be adopted to treat these cases. OBJECTIVES: To evaluate functional outcome of simultaneous arthroscopic ACL and PCL reconstruction with hamstring tendon autograft in multiligamentous knee injuries. PATIENTS AND METHODS: This prospective study was performed on 20 patients with combined ACL-PCL injuries who underwent simultaneous arthroscopic ACL-PCL reconstruction with hamstring tendon. Evaluation of functional outcome was by IKDC and Lysholm-Tegner scores. RESULTS: In 20 patients, mean age 34 years, return to full-time work and to full sports was 8 weeks and 6.2 months respectively. All patients had full range of motion except 2 patients with < 5 degrees flexion loss; 90% had negative Lachmann test; 95% had negative pivot shift and 10% patients had mild posterior drawer at 90 degrees (1+) at final follow up. Mean IKDC score was 90 (range 81 - 94); mean Tegner activity score was 7 and mean Lysholm knee score was 89. 85% returned to preinjury activity level and a 90% satisfaction rate. CONCLUSIONS: Simultaneous arthroscopic ACL and PCL reconstructions using hamstring tendon for combined ACL and PCL injuries is a clinically effective, safe, time saving and cost-effective procedure with better patient compliance and reproducible for a timely return of motion, strength, and function with favorable outcome.